(untitled) (Tzintzun, Revista de Estudios Históricos, 2016)
The independence movement included a period from 1808 to 1821, to understand it better, it is necessary to establish certain chronological sections related to the incidents in the metropolis, the policies implemented by the viceroys or prefects, the behavior assumed by the power groups, the insurgency and the deaths of their own leaders. Similarly, it is necessary to study the phenomenon on the basis of a regionalization. In this paper there is a review the situation where the insurgency was in one of their last strongholds: the lowlands of the province of Michoacan, after the restoration of the constitution of Cadiz in 1820. The return to constitutionalism and the backlash that took certain sectors in the New Spain to the liberal type projects that had arisen in the Peninsula, originated since that time, those groups that were enemies of the movement initiated by Hidalgo and Morelos and were also the main promoters of the full and final separation from Spain.